PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS DI KELAS VI SDN 064034 MEDAN - Rina Wati Lumban Gaol; Patri Jason Silaban; Eka Kartika Silalahi; Regina Sipayung; Darinda Sofia Tanjung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Problem Based Learning learning model on student learning outcomes in the learning of Natural and Social Sciences (IPAS) in class VI SD Negeri 064034 Medan Learning Year 2024/2025. This study used a quantitative method with a pretest-posttest experimental design in one group, involving 28 students as samples. Data collection was carried out through learning outcome tests and student participation questionnaires that had been tested for validity and reliability. The pretest results showed the average value of student learning outcomes of 57.7 with a low category, while the posttest results increased to 77.43 with a high category. The Pearson correlation test produced a coefficient of 0.850 with a significance of 0.000, which indicates a strong positive relationship between the application of the PBL model and student learning outcomes. Furthermore, the results of hypothesis testing using the t-test obtained a tcount ≥ ttable value of 5.957 ≥ 2.048, which means that there is a significant influence between the use of the Problem Based Learning learning model on student learning outcomes. Thus, the research hypothesis which states that there is a significant effect of the Problem Based Learning learning model on student learning outcomes.